Über die Form von Fluß-Spiegeln und ihre geomorphologische Bedeutung - Louis, Herbert (ERDKUNDE, 1966)
The so-called equilibrium of rivers is not so well defined as to allow far reaching conclusions about the morphogenous effect of rivers considered to be in a state of equilibrium. The author thinks that accurate observations about the surface of rivers give a better indication of how to approach this problem, as it is possible to state that the general gradient and any other permanent deformation of a river's surface indicate a local change in the water's potential energy. Four types of river surfaces may be distinguished: 1. The flat river surface. This is characteristic of rivers flowing with moderate turbulence. At times of calm the unevenness of the surface is quite insignificant. Flat spots (Quellfladen), resulting from upwelling water, and small eddies (Sogtrichter) are to be seen moving with the current. Variations in the supply of energy result from very small, hardly perceptible, alterations of surface gradient. 2. The almost flat river surface. This has more vigorous upwell spots (Quellbuckel) surrounded by marked undertow margins moving with the current. In addition there are wandering ripples which may even be sufficiently steep to give rise to foaming. Nevertheless, the gradient of the river surface is not deformed by any stationary break nor by permanent stretches of opposite gradient. Thus the almost flat river surface is also indicative of a balanced energy supply throughout the river. 3. The irregularly deformed river surface. This type is characterised by stationary surface breaks over the whole width of the river and in irregular arrangement, and/or by having permanently some parts of the surface with opposite gradients. Its movement is rushing (schiefiend). The energy supply between neighbouring points of the river is no longer balanced. It is not possible to say whether the Talweg (long profile) of the river is in the process of becoming more irregular or more regular. This is an ungraded river. 4. Between the almost flat river surface and the irregularly deformed river surface there is the regularly, deformed river surface. It has stationary waves grouped in regular patterns and the movement of the water is a rushing one. Because of the stationary waves the long profile of the river surface is not strictly speaking continuously sloping. However we can deduce from the adjustment of the surface deformations that the energy supply of adjoining points of the river must nevertheless be balanced. Thus a regularly deformed river surface also indicates a graded river. Some further remarks deal with the influence which is exerted upon the form of the river surface by the water level. Finally it is explained that observations upon the type of river surface are to be combined with data of discharge, velocity, gradient and the character of the river bed.